Towards Automation in Admission Process as a Tool to Enhance Quality of Engineering Education at Tribhuvan University - Dawadi, Babu Ram; Baral, Daya Sagar (Journal of the Institute of Engineering, 2018)
Institute of Engineering (IOE), Tribhuvan University (TU) is the government owned oldest institution in Nepal providing quality education in the engineering domain since 1972. However in the recent decade, other several universities are established in the country, IOE hasn’t lost its popularity with its major features to have dedication on quality education to fulfill the world class education. As a public institution, it provides equal opportunities for all qualified citizens to enter into the university education. With the increasing number of affiliated colleges and applicants, the entrance exam and admission system are becoming challenging. Accepting the challenges, IOE adapted online applications and admit card generation with computer based entrance exam since 2014. Since recent past years, the student pass rate in the semester exams is not satisfactory. It raised the quality issues and required to find the causes so as to enhance quality. However there are several factors that affect the education quality, we identified that the admission process followed in most of the affiliated colleges is partially in the meritorious basis that affects the semester exam results. From this paper, we analyzed the past admission process and the student’s status in semester exam where we tried to co-relate the quality intake in entrance exam and the semester exam of IOE. We proposed an optimal technical framework to admit merit based applicants through online centralized admission system that helps to overcome the admission challenges and enhance the quality of engineering education of IOE.Journal of the Institute of Engineering, 2017, 13(1): 48-59